Expression of c-fos Was Associated with Clinicopathologic Characteristics and Prognosis in Pancreatic Cancer - Guo, Jun-Chao (PLoS One, 2015)
It has long been regarded that pancreatic cancer (PC) is a life-threatening malignant tumor. Thus, much attention has been paid for factors, especially relative molecules, predictive for prognosis of PC. However, c-fos expression in PC was less investigated. In addition, its association with clinicopathologic variables and prognosis remains unknown. In the present study, expression of c-fos was detected by tissue microarray-based immunohistochemical staining in cancer and adjacent tissues from 333 patients with PC. The staining results were correlated with clinicopathologic parameters and overall survival. Furthermore, prognostic significance of c-fos in subsets of PC was also evaluated. It was shown that low expression of c-fos was more often in cancer than in adjacent tissues of PC (P<0.001). Besides, high cancerous c-fos expression was significantly associated with tumor site and T stage, whereas peri-neural invasion was of a borderline significant relevance. Log-rank test revealed that high expression of c-fos in cancer tissues was a significant marker of poor overall survival, accompanied by some conventional clinicopathologic variables, such as sex, grade, peri-neural invasion, T and N stages. More importantly, cancerous c-fos expression was identified as an independent prognosticator in multivariate analysis. Finally, the prognostic implication of c-fos expression was proven in four subsets of patients with PC. These data suggested that c-fos expression was of relationships with progression and dismal prognosis of PC.